Patient's perspective on improving the quality of acute medical care: determining patient reported outcomes. Issue 3 (29th September 2019) - Kremers, Marjolein N T; Zaalberg, Tessel; van den Ende, Eva S; van Beneden, Marlou; Holleman, Frits; Nanayakkara, Prabath W B; Haak, Harm R
Abstract : Rationale: There is an increasing societal demand for quality assurance and transparency of medical care. The American National Academy of Medicine has determined patient centredness as a quality domain for improvement of healthcare. While many of the current quality indicators are disease specific, most emergency department (ED) patients present with undifferentiated complaints. Therefore, there is a need for generic outcome measures. Our objective was to determine relevant patient reported outcomes (PROs) for quality measurement of acute care. Methods: We conducted semistructured interviews in patients ≥18 years presenting at the ED for internal medicine. Patients with a cognitive impairment or language barrier were excluded. Interviews were analysed using qualitative content analysis. Results: Thirty patients were interviewed. Patients reported outcomes as relevant in five domains: relief of symptoms, understanding the diagnosis, presence and understanding of the diagnostic and/or therapeutic plan, reassurance and patient experiences. Experiences were often mentioned as relevant to the perceived quality of care and appeared to influence the domain reassurance. Conclusion: We determined five domains of relevant PROs in acute care. These domains will be used for developing generic patient reported measures for acute care. The patients' perspective will be incorporated in these measures with the ultimate aim of organising truly patient-centred care at the ED.